A novel bidirectional complementary-type inchworm actuator with parasitic motion based clamping. (1st December 2019) - Wang, Yue; Yan, Peng
Highlights: A bidirectional complementary-type inchworm actuator with reduced drive electronics. Actuator is driven by longitudinal deformation and clamped by parasitic motion. Adjustable preload capable of optimizing the step consistency and loading capacity. Experimental results show high driving speed and low motion coupling of the design. Abstract: In this paper, a novel bidirectional complementary-type inchworm actuator is developed with the help of two piezo-stacks (PZTs), where a simpler structure is obtained by employing the longitudinal deformation and parasitic motion for driving and clamping, respectively. In particular, the proposed actuator is designed with two complementary clamps: one composed of lever mechanism is referred to as normally clamped (NC), while the other one composed of bridge-type mechanism is referred to as normally unclamped (NU). Static models on the clamping force and step length are also discussed to describe the bidirectional motion sequences. Various experiments are conducted based on a fabricated prototype to investigate the driving characteristics and system performance, where the operating principle of the proposed design and the modeling methods are effectively evaluated. Comparing with existing results, the proposed actuator achieves a reduced coupling motion of 4 % and relatively high driving speed (216.3 μm/s) with only two PZTs. In addition, the proposed design has an adjustable preload capable of optimizing the step consistency and loading capacity for long stroke nano-positioning purposes.